1999
DOI: 10.1074/jbc.274.24.17209
|View full text |Cite
|
Sign up to set email alerts
|

ErbB Receptor-induced Activation of Stat Transcription Factors Is Mediated by Src Tyrosine Kinases

Abstract: Epidermal growth factor (EGF) binding to its receptor, ErbB1, triggers various signal transduction pathways, one of which leads to the activation of signal transducer and activator of transcription (Stat) factors. The mechanism underlying ErbB1-induced Stat activation and whether Stats are downstream targets of other ErbB receptors have not been explored. In this report we show that ErbB2, ErbB3, and ErbB4 do not potentiate Stat5 phosphorylation by EGF. However, neu differentiation factor-induced heterodimers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
273
4

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(297 citation statements)
references
References 60 publications
20
273
4
Order By: Relevance
“…We also noted that constitutively activated STAT3 and STAT5 frequently coexisted in the same specimen. It has been shown that different STATs can be activated by the same ligand and/or intracellular tyrosine kinase (Ruff-Jamison et al, 1994;Carlesso et al, 1996;Olayioye et al, 1999). Simultaneously persistent STATs activation is also noted in a variety of human cancers (Turkson and Jove, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…We also noted that constitutively activated STAT3 and STAT5 frequently coexisted in the same specimen. It has been shown that different STATs can be activated by the same ligand and/or intracellular tyrosine kinase (Ruff-Jamison et al, 1994;Carlesso et al, 1996;Olayioye et al, 1999). Simultaneously persistent STATs activation is also noted in a variety of human cancers (Turkson and Jove, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Human epidermal growth factor receptor 2 (ErbB-2/HER2), one of the members of the ErbB family of membrane receptor tyrosine kinases, is a major player in the breast cancer scenario [1]. Membrane ErbB-2 (MembErbB-2) overexpression is associated with poor clinical outcome [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, a significant percentage of tumors display primary or acquired trastuzumab resistance [5]. Notably, the dogma of ErbB-2 action as a membrane tyrosine kinase which induces the activation of mitogenic signaling pathways to promote breast cancer growth [1], has been challenged by the demonstration that MembErbB-2 migrates to the nuclear compartment, where it acts as a transcription factor (TF) [6]. Up to date, cyclooxygenase-2 (COX-2) gene is the only one whose expression has been shown to be modulated through the role of ErbB-2 as a TF in mammary tumor cells [6].…”
Section: Introductionmentioning
confidence: 99%
“…Stat5a and Stat5b in hematopoietic cells seem to promote growth, inhibit apoptosis, and may be involved in malignant transformation (Matsumura et al, 1999;Nosaka et al, 1999;Demoulin et al, 2000), and are also essential mediators of the effects of prolactin (PRL) and growth hormone (GH) as well as IL-2 and other cytokines (Groner and Gouilleux, 1995;Grimley et al, 1999;Moriggl et al, 1999;Herrington et al, 2000;Lin and Leonard, 2000). However, although STAT proteins in some cells have been found to be phosphorylated and activated in response to growth factors, including EGF (Ruff-Jamison et al, 1993Richer et al, 1998;Guren et al, 1999;Luetteke et al, 1999;Olayioye et al, 1999), PDGF (Valgeirsdottir et al, 1998;Sachsenmaier et al, 1999), and VEGF (Bartoli et al, 2000), their exact function in receptor tyrosine kinase signaling has not been defined, and the role of STAT proteins in EGF receptor-mediated mitogenic mechanisms is not known.…”
mentioning
confidence: 99%